Normative Aesthetics: The Ideal Audience and Art Education - Sunaryono Basuki Ks (Universitas Negeri Malang, 2016)
Reader-Response Criticism proposes a new way of looking at literary text. One of the writers of this criticism discusses about 'literary competence' which entails the idea of 'ideal reader'. The writer proposes the idea of 'ideal audience' to work with fields of art other than literature. In an attempt to give the proper appreciation of art, norms are required, and norms in art can be arrived at using the concept of 'ideal audience'. It is a fact that norms are normally contextual, not universal, and change according to the change in the concept of art creation. Then the question is why take the trouble of forming norms if they keep changing?